Tech Trends Reshaping Tomorrow: A Glimpse into Organizational Technology Adoption - Rizkita Boyas, Jeziano; Prayudi, Deri; Givan, Bryan (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2024)
This study investigates the impact of emerging technologies, innovation culture, and employee training and development on organizational performance at PT Bias Nusatama. Utilizing a quantitative research design with a sample of 60 employees selected through random sampling, the research employs Smart PLS for data analysis. The results reveal that the direct effects of adopting emerging technologies and fostering an innovation culture significantly enhance organizational performance. Additionally, both factors indirectly influence performance through their effects on employee training and development. These findings emphasize the importance of integrating new technologies, nurturing an innovative culture, and investing in employee training to drive organizational success. The study provides valuable insights for organizations seeking to optimize their performance through strategic technology adoption and supportive work environments.